2006
DOI: 10.1007/bf03327557
|View full text |Cite
|
Sign up to set email alerts
|

Decision-making in obesity: A study using the Gambling Task

Abstract: The present study addresses the issue of whether a "decision-making disorder" could account for the behavioral problems of severely obese patients (BMI score >34) who are not classified by traditional psychiatric Eating Disorder tests. The neuropsychological test employed, the Gambling Task (GT), is not directly related to the food domain, but it is sensitive to failure in making long-term advantageous choices. A comparison was made of 20 obese subjects (OS) and 20 normal-weight subjects (NWS) matched in age, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
76
0
5

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(89 citation statements)
references
References 37 publications
8
76
0
5
Order By: Relevance
“…Though neuropsychological studies on obesity are limited and the findings are confounded by the medical complications of obesity (i.e diabetes and hypertension), there is evidence that in obese subjects inhibitory control may be disrupted. Specifically, when compared with normal weight individuals, obese subjects make less advantageous choices, which is a finding consistent with impaired inhibitory control and with prefrontal dysfunction (Pignatti et al, 2006). Moreover rates of attention deficit hyperactivity disorder (ADHD), which involves disruption in impulsivity, are elevated in obese individuals (Altfas, 2002).…”
Section: Study Limitationsmentioning
confidence: 84%
“…Though neuropsychological studies on obesity are limited and the findings are confounded by the medical complications of obesity (i.e diabetes and hypertension), there is evidence that in obese subjects inhibitory control may be disrupted. Specifically, when compared with normal weight individuals, obese subjects make less advantageous choices, which is a finding consistent with impaired inhibitory control and with prefrontal dysfunction (Pignatti et al, 2006). Moreover rates of attention deficit hyperactivity disorder (ADHD), which involves disruption in impulsivity, are elevated in obese individuals (Altfas, 2002).…”
Section: Study Limitationsmentioning
confidence: 84%
“…33 Studies focused on decision-making tasks have shown that, when an excessive load was placed on a subject's working memory, he or she found it difficult to fully integrate relevant information, thus leading him or her to make choices based solely on the immediate rewards as opposed to the overall information he or she had accumulated from past experiences. 7,8,33 Previous studies 34,35 with obese individuals reported that their decisionmaking ability proved to be poor (as assessed by a validated computerized gambling task) because they chose to behave according to immediate rewards even if faced with future longterm negative consequences. It has been suggested that overeating is not simply a passive response to salient environmental triggers and powerful physiological drives.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals with excess weight were evaluated by a physician for exclusion criteria, which included significant medical or psychiatric illness, and current treatment with medication; their characteristics are shown in Table 1. Normal-weight adolescents (BMI range [17][18][19][20][21][22][23][24] were recruited through schools located in the same geographical area, from families with similar sociodemographic background to the ones forming the clinical group.…”
Section: Methods and Procedures Subjectsmentioning
confidence: 99%
“…A study in a large sample of healthy adults demonstrated that increased BMI was associated with poorer performance on tests of response inhibition and flexibility (17), whereas a recent study showed that individuals seeking surgical treatment for obesity (BMI ≥40) had significantly impaired performance on the Rey-Osterrieth complex figure test and the Wisconsin card sorting test (tests indexing planning/memory and flexibility) as compared to normative values (18). Studies on adults with excess weight have also demonstrated an association between BMI and performance on a decision-making test known as the Iowa gambling task (IGT) (19,20), but no studies have examined this process on adolescents with excess weight. The aim of this study is to explore neuropsychological performance of adolescents with excess weight vs. normal-weight adolescents on a comprehensive battery of executive functioning tests, including measures of working memory, analogical reasoning, planning, response inhibition, flexibility, self-regulation, and emotional decision-making.…”
Section: Articlesmentioning
confidence: 99%